Endonasal Rhinoplasty Alters Nasal Anatomy Without Resulting in Visible Scarring - Rodríguez Navarro (Multidisciplinary Journal of Akseprin Indonesia, 2025)
Endonasal rhinoplasty, or closed rhinoplasty, is a surgical technique employed to alter the nasal architecture for cosmetic or functional reasons while avoiding visible scarring. The primary benefit is the attainment of natural results with a more rapid recovery relative to alternative approaches. This surgical technique necessitates exceptional precision and a comprehensive knowledge of nose anatomy, integrating technical expertise with an artistic viewpoint. It has demonstrated efficacy throughout time, offering numerous advantages, including decreased postoperative edema and a shorter recovery duration. This article elucidates the endonasal rhinoplasty procedure, emphasizing its significance and efficacy without juxtaposing it with open rhinoplasty, as both possess distinct indications. It underscores the necessity for surgeons to proficiently learn both techniques to offer solutions customized to the specific requirements of patients. A clinical case is described with a 21-year-old female patient who desired enhancement of her nasal profile due to a dorsal hump and a ptotic tip. A closed rhinoplasty was conducted under general anesthesia in a suitable surgical environment, resulting in a pleasing aesthetic outcome and a smooth postoperative recovery. Presently, endonasal rhinoplasty is a pivotal method in the worldwide movement of preservation rhinoplasty, emphasizing the maintenance of nasal structures to guarantee enduring and aesthetically pleasing outcomes